Perlindungan Hukum Terhadap Pekerja Anak (Child Labor) Di Indonesia - Nadila Oktavianti; Nahdhah Nahdhah (Scholar Center, 2021)
This study aims to determine the protection of child laborers in Indonesia, especially the rules protecting child labor. The research method used is legal research with a statute approach (statutory approach) which is analyzed by normative analysis. Children are prohibited from working in order to guarantee protection for working children. Various laws and regulations have been issued, which in principle prohibit children from working and if they are forced to work, then normatively these children must obtain adequate legal protection guarantees. Right to get education (Article 9 of Law Number 35 Year 2014), Right to get occupational safety and health (Article 74). Exploitation of children is also inseparable from other legal instruments, namely Law Number 23 of 2002 concerning Child Protection. Basically, every child, while in the care of a parent, guardian, or any other party responsible for care, has the right to receive protection from treatment, one of which is protection from exploitation, both economic and sexual. Thus, among others, what is regulated in Article 13 paragraph (1) letter b of the Child Protection Law. It is further regulated in Article 76I of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection (“Law 35/2014”), it is stipulated that every person is prohibited from placing, allowing, doing, ordering to do, or participate in exploiting children economically. The sanctions for violations of Article 76 I are regulated in Article 88 of Law 35/2014, namely the offender is sentenced to imprisonment for a maximum of 10 (ten) years and / or a maximum fine of Rp.200,000,000.00 (two hundred million rupiah). Thus, it means that employers and parents who employ children in the world with the aim of being exploited economically are punishable under Article 88 of Law 35/2014. The results showed that child laborers have received sufficient protection from the laws and regulations in Indonesia. This protection is at the level of basic state laws (contitutions) and laws, as well as in derivative regulations issued by the central government, ministers and local governments.